Connecting Adult Learning and Knowledge Management Strategies for Learning and Change in Higher Education and Organizations - Fedeli, Monica; Bierema, Laura L. (Knowledge Management and Organizational Learning, 2019)
XV, 248 p. 31 illus., 17 illus. in color.